Clinical Factors Related to Improved Scapular Control After a Scapular Conscious Control Program in Symptomatic Overhead Athletes: Secondary Analysis of a Randomized Controlled Trial. Issue 11 (26th November 2020) - Huang, Tsun-Shun; Du, Wan-Yu; Lin, Jiu-Jenq
Background: Predictive variables associated with the effects of a scapular conscious control program should be identified and used to guide rehabilitation programs. Purpose: To determine whether potential factors are associated with the success of scapular muscle balance with an early control program in patients with subacromial pain and scapular dyskinesis. Study Design: Case-control study; Level of evidence, 3. Methods: A total of 38 amateur overhead athletes with subacromial pain and medial border prominence were recruited. They performed progressive conscious control of scapular orientation during 45° and 90° of arm elevation. Stepwise logistic regression and receiver operating characteristic curve were used to determine the optimal cutoff point of related factors for success or failure of the program. Potential factors including pain level during activity, pain duration, anterior/posterior shoulder flexibility, forward shoulder posture, posterior displacement of root of spine and inferior angle, scapular kinematics, and muscle activation before conscious control program were recorded as independent variables. Successful control defined as decreases of the upper trapezius/serratus anterior ratio in 2 consecutive trials of the 90° program or failure in the program was used as a dependent variable. Results: Having a posterior displacement of the inferior angle of the scapula of ≤16.4 mm and scapular posterior tipping during arm elevation of ≤3.3° (collected before the control program) were associated with the success of the program ( R 2 = 0.286; P < .05). Additionally, participants with each or both variables present at baseline had probabilities of success of 78% and 95%, respectively. Conclusion: The value of scapular posterior displacement and posterior tilt should be considered before early scapular control program. Other factors related to the success of the program should be found due to the limited variance explained in the regression model.